DNA-directed coimmobilization of multiple enzymes on organic−inorganic hybrid DNA flowers - Li, Yali; Wang, Jing; Huang, Fenghong; Zhang, Yufei; Zheng, Mingming (Frontiers in Bioengineering and Biotechnology, 2022)
The artificial multienzyme systems developed by mimicking nature has attracted much interest. However, precisely controlled compositions and ratios of multienzymatic co-immobilization systems are still limited by the indistinguishable nature of enzymes. Herein, a strategy for fabricating DNA-directed immobilization of horseradish peroxidase (HRP) and glucose oxidase (GOx) on hybrid DNA nanoflowers (GOx-HRP@hDFs) is presented. The preparation of micron-sized hybrid DNA flowers (hDFs) begins with the predetermined repeatable polymer-like DNA sequences which contained two strands. The hDFs structure is generated through one-pot rolling circle amplification (RCA) and self-assembly with magnesium pyrophosphate inorganic crystals. Based on the rigid-base pairing, GOx and HRP conjugated with sequences complementary to strands would be anchored to the predesigned locations, respectively. By adjusting the loading amount/ratio of enzymes properly, the maximal catalytic efficiency can be precisely regulated. The reaction activity of GOx-HRP@hDFs was 7.4 times higher than that of the free GOx-HRP under the optimal mole ratio (GOx/HRP 4:1). In addition, this multienzyme catalyst system exhibits excellent precision, specificity, reproducibility, and long-term storage stability when applied to real human blood samples. The preceding results validate that GOx-HRP@hDFs are promising candidates for personal diabetes detection.